Features of technical and tactical actions of the team "Metalist" in the games of the League of Europe - Перевозник, Владимир; Паевский, Владимир (Slobozhanskyi Herald of Science and Sport, 2018)
Vladimir Perevoznik & Vladimir Paevskiy Purpose: to analyze the technical and tactical actions (single combats, selection, interceptions) of the "Metalist" in the games of the Europa League in 2011–2012. Material & Methods: study was carried out using the method of expert assessments. Analyzed 7 games of the League of Europe. Results: average indicators of technical and tactical actions (single combats, selection, interceptions) of the "Metalist" team in the games of the Europa League in 2011–2012 have been analyzed, the average indicators for the 1st and 2nd half and for the game as a whole have been determined. The rejection coefficient is calculated. Conclusion: quantitative and qualitative indicators of technical and tactical actions (single combat, selection, interception) of the "Metalist" in the games of the Europa League.